Biodiesel production from Cynara cardunculus L. and Brassica carinata A. Braun seeds and their suitability as fuels in compression ignition engines - De Domenico, Stefania; Strafella, Luciano; D'Amico, Leone; Mastrorilli, Marcello; Ficarella, Antonio; Carlucci, Paolo; Santino, Angelo (Italian Journal of Agronomy, 2016)
The development of energy crops can provide environmental benefits and may represent an opportunity to improve agriculture in areas considered at low productivity. In this work, we studied the energy potential of two species (Brassica carinata A. Braun and Cynara cardunculus L.) and their seed oil productivity under different growth conditions. Furthermore, the biodiesel from the oil extracted from the seeds of these species was produced and analysed in term of utilisation as fuels in compression ignition engines. In particular, the spray penetration and shape ratio were measured in a constant-volume chamber and compared with the results obtained with a standard diesel fuel. These results were obtained using a standard common rail injection system at different injection pressure, injection duration, and constant-volume chamber pressure.